Challenges to american leadership in the 20th and 21st century and the emergency of chinese e-commerces - Jesus, Fernando Soares de (2023)
This article aims to understand the emerging e-commerce in its relationship with the economic logic placed between the end of the 20th century and the beginning of the 21st century, especially after the rise of China as a political and economic power. To this end, we employ the understanding of long cycles, created by Nikolai Kondratiev and organized by Schumpeter (1939). As research techniques, analyzes were carried out on the financial reports of companies in the sector, and on data systematized by specialized consultants. As a result, the American company Amazon Inc. attempts to internationalize, especially in emerging markets, while Chinese companies, notably Alibaba, focus on strengthening the domestic market.